2021
DOI: 10.1155/2021/1837458
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Treatment of Severe Ptosis by Conjoint Fascial Sheath Suspension

Abstract: Objective. To explore the role of conjoint fascial sheath (CFS) suspension in the treatment of severe ptosis. Methods. A total of 110 patients with severe ptosis who were admitted to our hospital from May 2018 to December 2020 were included. Fifty-seven patients treated with frontalis suspension were assigned into group A, and the remaining 53 patients treated with CFS suspension were assigned into group B. The curative effect, ocular surface alterations, complications, and satisfaction in the two groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The mean MRD1 of group A at the last visit was 3.00 ± 0.69 mm, which approximates the result of 3.10 ± 0.22 (22). The corrective effect was 77.78% at the last visit in group A, which is better than the result of 67.92% in a previous report (23). In view of the long-term outcomes after the operation, there was no significant difference between group A and group B.…”
Section: Discussionsupporting
confidence: 44%
“…The mean MRD1 of group A at the last visit was 3.00 ± 0.69 mm, which approximates the result of 3.10 ± 0.22 (22). The corrective effect was 77.78% at the last visit in group A, which is better than the result of 67.92% in a previous report (23). In view of the long-term outcomes after the operation, there was no significant difference between group A and group B.…”
Section: Discussionsupporting
confidence: 44%
“…Histologically, CFS is composed of thick collagen bundle and confluent elastic fibers without any smooth muscles. Due to its tough nature, it has been used successfully in open, anterior approach of blepharoptosis surgery [7][8][9][10][11] . In this research, we have further developed this technique and used the CFS as a fixation point from which to suspend the tarsus using sutures.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2002, CFS suspension surgery has been used to correct ptosis ( 3 ). In CFS surgery, the CFS is fixed at the anterior one-third of the tarsus so that the upper eyelid margin of the affected eye is located at the upper edge of the cornea when looking straight ahead in a sitting position to serve as a corrective role ( 4 ). This surgery is now recognized in clinical practice due to good efficacy and a low number of complications, such as lagophthalmos, exposure conjunctivitis and hematoma in the eyebrow area ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This surgery is now recognized in clinical practice due to good efficacy and a low number of complications, such as lagophthalmos, exposure conjunctivitis and hematoma in the eyebrow area ( 5 ). However, a number of patients experience upper eyelid retraction after surgery, and Sang et al ( 4 ) reported that the amount of upper eyelid retraction was 0.21±0.07 mm 3 months after surgery. CFS suspension alone lacks strong attachment points, so it cannot maintain long-term tissue tension.…”
Section: Introductionmentioning
confidence: 99%